Slot antenna array for fifth generation metal frame mobile phone applications. Issue 9 (30th May 2019) - Huang, Daiwei; Du, Zhengwei; Wang, Yan
Abstract: An eight‐element antenna array based on open/closed slot modes that can cover the 3.5 GHz band (3400‐3600 MHz) is proposed and studied. There are two kinds of antenna elements with the slot sizes of 10.8 × 1 mm 2 and 28.8 × 1 mm 2 for open and closed slot modes, respectively. Both the two kinds of antenna elements are realized with the help of the metal frames with the height of 7 mm at the two long sides of the ground. The proposed antenna array is suitable for 5G metal frame mobile phone applications. A prototype is fabricated and measured. The measured results show that all the eight antenna elements can cover the band of 3400‐3600 MHz and the isolations are bigger than 13 dB, the measured efficiencies all are bigger than 42% and the measured envelope correlation coefficients are lower than 0.15.